On the variability in Fo patterning and the function of Fo timing in languages where pitch cues stress - Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1982)
The basic property of pitch as a cue to linguistic stress is fundamental frequency (Fo) change. That leaves room for a lot of variation: in the direction of the change, the amount of change, and its exact coordination with the stressed syllable. Examples (from the literature) from a number of languages and dialects attest that they do indeed exhibit quite striking differences in the stress/Fo relationship. The decisiveness, under certain circumstances, of the timing of Fo events is illustrated by the results of a pilot experiment with a disyllabic Danish word: the location of a two semitone rise from the first to the second syllable - before or after the intervocalic sonorant consonant - will shift listeners' location of the stress.